DEVELOPMENT OF SMALL AND MEDIUM ENTREPRENEURSHIP IN AGRARIAN SPHERE OF KAZAKHSTAN - K.M. Utepkalieva, K.M. Utepkalieva; Sabirova , R.K; Kabdulova, A.S. (Academic Journal of Physical and Chemical Sciences, 2018)
Effective activities of the country's agro-industrial complex are closely interrelated with the proportional development of its constituent branches. A special place in this system is export, the sphere of production, processing and marketing of agricultural products, the level of development and functioning of which determines the livelihood of the population, achieving a balance in the agrarian sector of the republic. The process of integration into the world market has puzzled food security, which entailed not just the creation of a developing agricultural sector in the economy, but, above all, the creation of an efficient processing complex. As the President of the Republic of Kazakhstan N.A. Nazarbayev "a republic with a high potential for agricultural development can be among the world leaders in the production and processing of agricultural products. The development of Kazakhstan's export is of particular importance, serving as an important element of the country's long-term strategy. It is the export potential of the economy that contributes to higher incomes of the population, to the rapid development of market infrastructure, to identify the strengths and weaknesses of the national industry.